Using the QR code as a means of automating the process of accounting for attendance at educational classes - Stupina, M V; Anistratenko, K V; Pazina, L O (Journal of physics. Conference series, 2021)
Nowadays, the technology of QR codes is one of the promising areas of development of the IT industry, which has found application in various industries, business areas, medicine, etc. In the field of education, QR codes are used to increase the interactivity of classes, provide additional multimedia content, conduct surveys and other control activities. This work presents the key features of QR codes, their architecture and main components. The use of QR codes in automating the process of accounting for students’ attendance is considered. A web application has been developed for teachers, the interface of which allows them to generate QR codes for academic disciplines. A mobile application with an integrated QR-code scanner was developed for students. All attendance data is recorded in the teacher’s electronic attendance register. A conceptual data model of the system is presented, as well as the main algorithms of its operation related to the generation and scanning of QR codes. The practice of using the developed system demonstrates the effectiveness of monitoring attendance data by promptly entering it into an electronic journal.